Digital tools/eHealth to support CKD self-management: A qualitative study of perceptions, attitudes and needs of patients and health care professionals in China. (September 2022) - Shen, Hongxia; van der Kleij, Rianne; van der Boog, Paul J.M.; Wang, Wenjiao; Song, Xiaoyue; Li, Zhengyan; Brakema, Evelyn; Lou, Xiaoping; Chavannes, Niels
Highlights: Map context factors. eHealth education. Use eHealth to partially replace care elements. Stakeholder involvement. Abstract: Background: A growing body of evidence supports the potential effectiveness of electronic health (eHealth) self-management interventions in improving disease self-management skills and health outcomes of patients suffering from chronic kidney disease (CKD). However, current research on CKD eHealth self-management interventions has almost exclusively focused on high-income, western countries. Objective: To inform the adaptation of a tailored eHealth self-management intervention for patients with CKD in China based on the Dutch Medical Dashboard (MD) intervention, we examined the perceptions, attitudes and needs of Chinese patients with CKD and health care professionals (HCPs) towards eHealth based (self-management) interventions in general and the Dutch MD intervention in specific. Methods: We conducted a basic interpretive, cross-sectional qualitative study comprising semi-structured interviews with 11 patients with CKD and 10 HCPs, and 2 focus group discussions with 9 patients with CKD. This study was conducted in the First Affiliated Hospital of Zhengzhou University in China. Data collection continued until data saturation was reached. All data were transcribed verbatim and analyzed using a framework approach. Results: Three themes emerged: (1) experience with eHealth in CKD (self-management), (2) needs for supporting CKD self-management with the use of eHealth, and (3) adaptation and implementation of the Dutch MD intervention in China. Both patients and HCPs had experience with and solely mentioned eHealth to 'inform, monitor and track' as potentially relevant interventions to support CKD self-management, not those to support 'interaction' and 'data utilization'. Factors reported to influence the implementation of CKD eHealth self-management interventions included information barriers (i.e. quality and consistency of the disease-related information obtained via eHealth), perceived trustworthiness and safety of eHealth sources, clinical compatibility and complexity of eHealth, time constraints and eHealth literacy. Moreover, patients and HCPs expressed that eHealth interventions should support CKD self-management by improving the access to reliable and relevant disease related knowledge and optimizing the timeliness and quality of patient and HCPs interactions. Finally, suggestions to adaptation and implementation of the Dutch MD intervention in China were mainly related to improving the intervention functionalities and content of MD such as addressing the complexity of the platform and compatibility with HCPs' workflows. Conclusions: The identified perceptions, attitudes and needs towards eHealth self-management interventions in Chinese settings should be considered by researchers and intervention developers to adapt a tailored eHealth self-management intervention for patients with CKD in China. In more detail, future research needs to engage in co-creation processes with vulnerable groups during eHealth development and implementation, increase eHealth literacy and credibility of eHealth (information resource), ensure eHealth to be easy to use and well-integrated into HCPs' workflows.